Teknik Permainan Solis Marimba dan Vibraphone pada Pertunjukan Concerto In F Mayor Autumn, Satellite Of Zapin, dan Exsplosive (Marimba and Vibraphone Solis Playing Techniques in Concerto In F Major Autumn, Satellite Of Zapin, and Explosive Performance) - Novaliano Novaliano; Andranofa Andranofa; Wilman Ismira Novatianus (MUSICA : Journal of Music, 2022)
Jurnal ini bertujuan untuk memberikan gambaran mengenai pertunjukan solis marimba dengan menerapkan teknik-teknik permainan perkusi serta interpetasi sebagai seorang solis pada repertoar Concerto in F major Rv.293 op.8 no.3 Autumn (L'Autumno) karya Antonio Lucio Vivaldi, Satellite Of Zappin karya dari grup musik melayu Riau Rhythm Chambers dan Exsplosive karya Tonci Huljic yang dipopularkan oleh Bond. Adapun teknik-teknik yang dipakai dalam penyajian karya-karya  tersebut antara  lain; single stroke, double stroke, pengungkapan ekspresi dan dinamika. Metode yang penyaji gunakan dalam artikel ini adalah deskriptif analisis terhadap karya yang dimiankan baik dari aspek teknik dan proses latihan menggunakan etude Goldenberg. Eksplorasi penerapan teknik yang diperoleh dari proses latihan individu menggunakan etude digunkan untuk pencapaian interpretasi dalam penerapan ekspresi terhadap karya. Hasil dalam artikel ini adalah teknik permainan yang digunakan dalam pertunjukan serta analisis interpretatif terhadap karya yang dimainkan dalam pertunjukan solis Marimba dan Vibraphone Concerto In F Mayor Autumn, Satellite Of Zapin, dan Exsplosive.ABSTRACTThis journal aims to provide an overview of marimba solo performances by applying percussion techniques and interpretation as a soloist in the repertoire of Concerto in F major Rv.293 op.8 no.3 Autumn (L'Autumno) by Antonio Lucio Vivaldi, Satellite Of Zappin by the Malay music group Riau Rhythm Chambers and Explosive by Tonci Huljic popularized by Bond. The techniques used in the presentation of these works include; single stroke, double stroke, expression and dynamics disclosure. The method that the presenter uses in this article is descriptive analysis of the work performed both from the technical aspect, and the training process using the Goldenberg etude. Exploration of the application of techniques obtained from the individual training process using etude is used to achieve interpretation in the application of expression to the work. The results in this article are the game techniques used in the performance as well as interpretive analysis of the works played in the solo performances of Marimba and Vibraphone Concerto In F Major Autumn, Satellite Of Zapin, and Exsplosive.